Competitive Advantage of German renewable energy firms in India and China - Holtbrügge, Dirk; Dögl, Corinna; Schuster, Tassilo (International Journal of Business and Emerging Markets, 2012)

Competitive advantage of German renewable energy firms in Russia - Holtbrügge, Dirk; Dögl, Corinna (Journal For East European Management Studies, 2010)
WiSo-Import:2015-03-26:472
Keywords: Transformation; Forschungsbericht 2010

Corporate environmental responsibility, employer reputation and employee commitment: An empirical study in developed and emerging economies - Dögl, Corinna; Holtbrügge, Dirk (International Journal of Human Resource Management, 2014)
Keywords: CER; CSR; employee commitment; employer reputation; signaling theory

Corporate environmental responsibility, employer reputation and employee commitment - Holtbrügge, Dirk; Dögl, Corinna (International Journal of Human Resource Management, 2014)
WiSo-Import:2015-03-26:5090

CRS in Emerging Economies - Holtbrügge, Dirk; Dögl, Corinna (Dictionary of Corporate Social Responsibility. CSR, Sustainability, Ethics and Governance, 2015)

How international is corporate environmental responsibility? - Holtbrügge, Dirk; Dögl, Corinna (Journal of International Management, 2012)
WiSo-Import:2015-03-26:3815

Innovations for Electro-mobility and Renewable Energies: Prospects for Chinese and German Firms - Holtbrügge, Dirk; Dögl, Corinna (Innovation for Green Growth, 2014)
WiSo-Import:2015-04-20:5099

Institutional Theory - Holtbrügge, Dirk; Dögl, Corinna (Dictionary of Corporate Social Responsibility. CSR, Sustainability, Ethics and Governance, 2015)

Stakeholder pressures, CSR practices, and business outcomes in Denmark, Germany and the Netherlands - Holtbrügge, Dirk; Dögl, Corinna; Berg, Nicola; Egri, Carolyn; Furrer, Olivier; Sinding, Knut (European Journal of International Management, 2018)
This cross-country study investigates the antecedents and outcomes of corporate social responsibility (CSR) practices. Based on institutional theory and stakeholder theory, we conducted an empirical study among 519 firms in Denmark, Germany and the Netherlands. We found evidence that supports a significant positive relationship between stakeholder pressures, CSR practices, and business outcomes in the total sample. While our data reveals similarities between the three countries, differences in some areas can be observed as well. Implications for institutional theory and for CSR are derive
Keywords: institutional theory; stakeholder theory; CSR; corporate social responsibility